Review of the genus Drylichus Heller (Insecta: Coleoptera: Dryopidae) - Kodada, Ján; Jäch, Manfred A.; Fedor Jr., Čiampor (Zootaxa, 2009)
The genus Drylichus Heller, which has not been treated since the original description in 1916, is reviewed taxonomically. The type species, Drylichus hylesinoides Heller (New Caledonia), is redescribed. Two new species, D. fidelitas sp. nov. (Lifou Island) and D. monteithi sp. nov. (New Caledonia), are described. Drylichus is hypothesized to be closely related with Parnida Broun (New Zealand), with which it shares the following characters: (1) shape of mouthparts and gular region, (2) distribution and morphology of sensilla on mouthparts, (3) configuration of antennomeres, (4) correspondence of several types of antennal sensilla, (5) shape of ventral sclerites of thorax and abdomen.